Primary care physicians’ views about gate-keeping in clinical research recruitment: a qualitative study - Guillemin, M; McDougall, R; Martin, D; Hallowell, N; Brookes, A; Gillam, L (Taylor and Francis, 2017)
Background: Clinical research is increasingly being undertaken in primary care. This development offers both benefits and challenges. The ethical challenges of occupying the roles of both clinician and researcher may be accentuated in primary care, where relationships are longer-lasting and medical conditions are less acute. This paper examines primary care physicians’ experiences of undertaking research, particularly their decision-making about recruiting patients in the context of their own dual roles. Methods: This project comprised in-depth interviews with eight Australian primary care physicians working in general or specialist practices that were involved in clinical research. Data were analyzed using inductive thematic analysis. Results: Physicians involved in recruiting their patients into clinical trials acted as gate-keepers; they were selective about which patients to recruit and did not necessarily approach all patients who met the research eligibility criteria. Physicians’ accounts suggested they prioritized their clinician role over their researcher role. In addition to the rigor and merit of the research, physicians considered the possible benefit of trial participation for individual patients. Physicians described making recruitment decisions based on their perceived knowledge of patients’ personal, behavioural, and attitudinal characteristics – often derived from their long-standing relationships with their patients. Conclusion: Our data shows evidence of gate-keeping by primary care physicians when deciding to participate in, and recruit their patients to, clinical studies. We argue that such gate-keeping is a way of addressing the dual and sometimes conflicting roles of clinician and researcher. It need not be ethically problematic, but primary care physicians should be reflexive about their recruitment practices and biases. In addition, this form of gate-keeping should be explicitly recognized in protocol design and the analysis of trial findings.